Interação fluido-estrutura usando a metodologia de fronteira imersa - Santos, Felipe Viegas (2017)
This dissertation introduces the development and implementation of a numerical tool to a solution of a newtonian incompressible flow problem, It was elaborated using the immersed boundary method that is commonly used in fluid-structure interactions, inthis case, there is an object immersed in the flow. The discretizations of the Navier- Stokes and temporal equations were performed for the Adams-Bashforth method. After, It was created an Eulerian and a Lagrangian mesh to work in the method of the mobile-least-squares reconstruction and in the Adams method, because the objective will be a simulate using both methods in a body immersed in the flow. Program implementation was performed by Python software and resulted in velocity, pressure and flow field graphs.